Factors Contributing to English Fluency Paucities among Secondary Level Students: Perspective Dinajpur Education Board, Bangladesh - Rana, Md. Sohel (Journal of Natural Language and Linguistics, 2024)
This study examines the factors contributing to English fluency paucity among secondary-level students in the Dinajpur Education Board, Bangladesh. Despite the prominence of English as a global language, students in this region face significant challenges in achieving fluency. The research identified key factors such as inadequate teaching methods, lack of exposure to English outside the classroom, limited access to English learning materials, socio-economic barriers, and insufficient emphasis on speaking and listening skills in the curriculum. Data was collected through surveys, interviews, and classroom observations, involving both students and teachers. The findings suggest that while students possess a basic understanding of English grammar and vocabulary, their ability to use the language in conversational settings remains limited. Furthermore, socio-cultural attitudes towards English and insufficient teacher training also play a role in hindering fluency development. The study recommends improvements in curriculum design, teacher professional development, and the promotion of interactive English language learning environments. Addressing these challenges could significantly enhance students’ fluency and better prepare them for academic and professional opportunities.